2013
DOI: 10.1504/ijiscm.2013.060974
|View full text |Cite
|
Sign up to set email alerts
|

A study of electronic commerce adoption factors in Nigeria

Abstract: Abstract:The paradigm shift to e-commerce in business transactions provides significant advantages such as expanding markets, improving customer services, reducing costs, and enhancing productivity. The global phenomenon is less aggressive in developing economies where small and medium enterprises struggle to provide internet services at their own expense due to limited government support and infrastructural deficiency. The acceptance of e-commerce adoption among Nigerians is slow irrespective of the huge popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…Stata 13 and SPSS version was utilized as the statistical tools, KMO sampling adequacy of .823 achieved, and alpha equal to .849 achieved. Thus, descriptive statistics presented (Oluyinka et al, 2013;Ayodele et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stata 13 and SPSS version was utilized as the statistical tools, KMO sampling adequacy of .823 achieved, and alpha equal to .849 achieved. Thus, descriptive statistics presented (Oluyinka et al, 2013;Ayodele et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The principal component analysis, factor loading accomplished as all loaded at expected column, AVE above .5, composite reliability and all cronbach's alpha of 0.7, p-values of .05, achieved (Hair et al, 2012;Oluyinka et al, 2013;Ayodele et al, 2018). Bootstrapped value and partial least square multiple weights (R 2 ) to explain the variance of the model adopted as recommended (Hair et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Relative advantage is extent condition to which innovation adoption is considered capable of providing greater benefits to organization than maintaining previous innovations [30]. Some studies have empirically identified relative advantage as a significant determinant of technology adoption [7,31]. Complexity indicators refer to conditions in which innovation adoption is considered relatively difficult or not to use [32].…”
Section: Influence Of Technology On E-commerce Adoptionmentioning
confidence: 99%
“…Indicators Descriptions References Technology: perceived behavior control, such as the cognitive skills of managers in using ecommerce technology and supporting resources is needed to exploit the potential of e-commerce technology Relative advantage the extent to which e-commerce technology is felt to provide greater benefits for SMEs than the ideas used previously [7,16,20,30,31] complexity the extent to which e-commerce technology is perceived as more difficult or too complex to be used than old ideas that have been used before [16,20,30,32] compatibility the extent to which e-commerce technology is felt in accordance with the needs, types of businesses and business processes that exist in SMEs [16,20,30,33,34] Organization: company characteristics and resources, such as the objectives of SMEs, readiness to use ecommerce technology and business size Top management support the extent to which the management of SMEs want to switch to using e-commerce and would allocate its resources to adopt ecommerce [16,23,37,48] Knowledge of information technology skills or knowledge of information technology from SME managers to be able to use e-commerce technology [16,39,40] size of organization the sufficient availability of resources owned by SMEs to adopt e-commerce technology [16,[41][42][43] Variables Indicators Descriptions References Environment: the condition of SME environment in carrying out its business processes and associated with the surrounding elements such as customers, competitors and presence of e-commerce technology service providers Competitive pressure the pressure experienced by SMEs from similar business competitors who have adopted e-commerce to gain a competitive advantage [23,45,48,49] Trading partners pressure willingness to gain trust in trading partners (buyers / customers) by providing valid product / service information and ease of product purchase transactions…”
Section: Variablesmentioning
confidence: 99%